Problematic internet use and its relationship with motor proficiency among adolescents participating in extracurricular sports (a comparative study of Indonesia and Latvia) - Nurulfa, Rizky; Klavina, Aija (Frontiers in Education, 2026)
IntroductionMotor proficiency and problematic internet use are increasingly viewed as intertwined facets of adolescent development, strongly influenced by physical activity and digital engagement; however, cross-cultural evidence distinguishing adolescents with and without extracurricular sports participation is still limited. This study aimed to examine and compare the relationship between motor proficiency (MP) and problematic internet use (PIU) in adolescents from in Indonesia and Latvia. Additionally, this study explored the association between healthy lifestyle behaviors, MP, and PIU among adolescents who participate extracurricular sports (ES) and non-sports (NS). This study utilized a cross-sectional research design.MethodsA total of 257 adolescents from Indonesia (n = 200) and Latvia (n = 57) completed the Problematic and Risky Internet Use Screening Scale (PRIUSS), four subtests from the Bruininks-Oseretsky Test of Motor Proficiency II (BOT-2), and self-reports on weekly PA and internet use. Group differences between NS and ES participants were analyzed using Mann–Whitney U tests. Associations between PIU and MP were examined with Spearman’s rho correlations and winsorized linear regression to limit the influence of extreme values (5th–95th percentiles).ResultsA significant negative correlation was found between PIU and MP in ES participants from Indonesia (rs = −0.367, p < 0.01). Meanwhile, regression analysis revealed a favorable correlation between physical activity and MP in Indonesia and Latvia, particularly among adolescents engaged in ES. In both countries, study-related and non-study-related internet usage were significant predictors for PIU, particularly among NS participants.DiscussionThe study found that participation in structured activities, such as ES, appears to support motor proficiency and reduce problematic internet use. Allocating time to regular physical activity and moderating leisure Internet use may protect adolescent health. These findings highlight the importance of context-specific strategies to promote active lifestyles and reduce risky digital behaviors.